Meaningful Relationships in Community and Clinical Samples: Their Importance for Mental Health - Block, Victoria J.; Haller, Elisa; Villanueva, Jeanette; Meyer, Andrea; Benoy, Charles; Walter, Marc; Lang, Undine E.; Gloster, Andrew T. (Frontiers in Psychology, 2022)
Meaningful relationships are centrally important for human functioning. It remains unclear, however, which aspects of meaningful relationships impact well-being the most and whether these differ between psychiatric patients and members of the community. Information about relationship attributes and functions were collected in community members (N = 297) and psychiatric patients (N = 177). Relationship attributes and functions were examined for differences between groups (community vs. patients), their impact on well-being and symptoms, and the size of network (one vs. many relationships). Community members reported fewer relationships, higher frequency of contact and less desire for change when compared to the psychiatric patients. Nevertheless, both groups reported relatively high levels of fulfilled functions. Quality of the relationship and investment into the relationship was associated with both well-being and symptoms for both the community and the patient group. Almost all functions were associated with well-being and symptoms for the community group. However, for the patient group, only few functions (sexual partner, go-to person for compassion, go-to person when happy) were associated with well-being and no functions were associated with symptoms. Contrary to our hypotheses, the results show that psychiatric patients do not have a deficit in fulfilling relationships. Most people report a well-functioning network of meaningful, high-quality relationships. Patients benefit from meaningful, function-fulfilling relationships just as much as community members. Results are discussed with respect to how targeting relationships can be used clinically.